Novel peripherally 4-[(6-Bromonaphthalene-2)-Oxy] substituted CoII, CuII, MnIII(Cl) phthalocyanines: Synthesis, characterization and biological activities - Kilicarslan, Fatma Aytan; Erdogmus, Ali; Yalcin, M. Serkan; Ozdemir, Sadin (SAGE PUBLICATIONS INC, 2026)
The aim of this work is to synthesize bis 4-[(6-bromonaphthalene-2)-oxy] substituted metal phthalocyanines at the peripheral positions and to investigate their biological properties. All synthesized compounds exhibited complete alpha-amylase inhibition activity 100% at a concentration of 100 mg/L. DNA interaction studies revealed that the compounds caused total degradation of DNA, as evidenced by gel electrophoresis analysis. Antimicrobial activity tests show that the complexes effectively inhibit the metabolic growth of the tested microorganisms. The minimum inhibitory concentration (MIC) values against Escherichia coli were determined as 32 mg/L for 4FFPcMn, 16 mg/L for 4FFPcCo, and 8 mg/L for 4FFPcCu. Additionally, 100% of E. coli cell viability was completely inhibited by all synthesized metallophthalocyanines, demonstrating their potent antimicrobial and photodynamic potential.
Keywords: phthalocyanine; antioxidant; antimicrobial; biofilm inhibition; cell viability; DNA cleavage; photodynamic therapy; Chemistry